Prediction of Oral Absorption of Low-Solubility Drugs by Using Rat Simulated Gastrointestinal Fluids: The Importance of Regional Differences in Membrane Permeability and Solubility - Yusuke Tanaka; Toshiyuki Baba; Koji Tagawa; Ryoichi Waki; Shunji Nagata (Frontiers Media S.A., 2014)
Purpose. This study aimed to develop a novel approach for predicting the oral absorption of low-solubility drugs by considering regional differences in solubility and permeability within the gastrointestinal (GI) tract. Methods. Simulated GI fluids were prepared to reflect rat in vivo bile acid and phospholipid concentrations in the upper and lower small intestine. The saturated solubility and permeability of griseofulvin (GF) and albendazole (AZ), a drug with low aqueous solubility, were measured using these simulated fluids, and fraction absorbed (Fa) at time t after oral administration was calculated. Results. The saturated solubility of GF and AZ, a drug with low aqueous solubility, differed considerably between the simulated GI fluids. Large regional differences in drugs concentration were also observed following oral administration in vivo. The predicted Fa values using solubility and permeability data of the simulated GI fluid were found to correspond closely to the in vivo data. Conclusion. These results indicated the importance of evaluating regional differences in drug solubility and permeability in order to predict oral absorption of low-solubility drugs accurately. The new methodology developed in the present study could be useful for new oral drug development.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.